Limiting factors for the use of palm oil biodiesel in a diesel engine in the context of the ASTM standard - Jalal Ghazanfari; Bahman Najafi; Sina Faizollahzadeh Ardabili; Shahaboddin Shamshirband (Cogent Engineering, 2017)
Biodiesel is a biodegradable fuel contains fatty acid methyl or ethyl esters which are typically produced by the transesterification reaction among the triglycerides in the vegetable oils or animal fats and an alcohol such as methanol or ethanol. There are many resources of biodiesel production. In present study it was selected the palm oil to produce the ethyl ester biodiesel and the limiting factors for the use of palm oil biodiesel in a diesel engine in the context of the ASTM standards were discussed. Based on results, the maximum engine power is obtained in maximum load of engine and indicates no sensible change in engine power for biodiesel blends. Increasing the engine load decreases the Brake Special Fuel Consumption (BSFC). The best BSFC accrues in the range of B10–B40. The engine efficiency is increased by increasing load. The best efficiency is observed in range of 50–100% of engine load and the best efficiency is in range of B10–B40. Generally, by considering three parameters of engine power, BSFC and engine efficiency the B10 fuel of palm biodiesel offers the best performance, therefore it can be the recommended fuel for this study.